« Les travaux pressants ». Calendrier agricole, assolement et productivité au Canada au XVIIIe siècle - Wien, Thomas (Revue d'histoire de l'Amérique française, 1990)
Les recherches de ces dernières années ont mis en lumière les ressemblances entre l'ancienne agriculture canadienne et celle de bien des paysanneries françaises de l’Ancien Régime. Dans un contexte comme dans l’autre, le marché étriqué et les forces de production peu développées créent un déséquilibre fondamental : trop de céréales, pas assez de bétail et donc pénurie de fumier. Ne pouvant amender leur terre de façon satisfaisante, les producteurs sont obligés de se contenter de rendements relativement faibles. De vieilles contraintes et non les vastes espaces de l’Amérique expliquent le caractère extensif de l’agriculture canadienne. Son originalité résulte donc de l’adaptation à d’autres particularités du nouvel environnement. Pour trouver des traces de cet ajustement, l’article étudie le régime d’assolement, élément-clé de l’agriculture paysanne qui exprime les contraintes du calendrier agricole. Il démontre que la coexistence de deux régimes différents dans la colonie est due à l’influence déterminante de la brève saison végétative sur la productivité.

Selling Beaver Skins in North America and Europe, 1720-1760: The Uses of Fur-Trade Imperialism - Wien, Thomas (Journal of the Canadian Historical Association / Revue de la Société historique du Canada, 1990)
Les historiens supposent généralement que pendant les dernières décennies du Régime français au Canada, la concurrence dans le commerce des fourrures suivait les lignes deforce de la rivalité impériale en Amérique du Nord. Situés sur la baie d'Hudson ou au sud du lac Ontario, les postes de l'empire adverse auraient constitué la principale menace pour les commerçants montréalais établis au coeur du pays indien. Cet article cherche les traces d'une telle concurrence à distance dans le commerce du castor. Il s'agit là d'une fourrure que les politiques de la Compagnie française des Indes rendaient moins chère dans le système commercial français que dans celui centré sur Londres. Or la distribution des recettes du castor entre les concurrents se montre peu sensible aux fluctuations dans cette différence intercoloniale des prix ; il semble bien que les marchands canadiens aient brandi l'épouvantait du concurrent étranger afin d'ajouter du poids à leurs demandes faites à l'Etat d'augmenter le prix du castor. Une conclusion s'impose : cette obsession d'un ennemi externe, transmise aux historiens par les sources officielles, a obscurci la dynamique interne du commerce canadien des fourrures au cours de cette période.

Guetter le rossignol : les voyages des ‘observations botanico-météorologiques’ entre la France, le Canada et l’Europe (1740-1775) - Wien, Thomas (Penser l'Amérique: de l'observation à l'inscription, 2017)

Introduction. Entre observation et inscription - Vuillemin, Nathalie; Wien, Thomas (Penser l'Amérique: de l'observation à l'inscription, 2017)

La "Prétendue Reppublique", pouvoir et groupes sociaux au Canada (1645-1672) - Horguelin, Christophe (Université de Montréal, 1994)

Introduction : la Nouvelle-France et l’Atlantique - Desbarats, Catherine; Wien, Thomas (Revue d’histoire de l’Amérique française, 2011)
Un article de la revue Revue d’histoire de l’Amérique française, diffusée par la plateforme Érudit.

Le Québec entre histoire connectée et histoire transnationale - Charles, Aline; Wien, Thomas (Globe : revue internationale d’études québécoises, 2011)
Histoire connectée, histoire transnationale, histoire croisée, histoire partagée, histoire « enchevêtrée » (entangled history) : toutes ces « histoires » s’intéressent aux flux ou mouvements (de personnes, d’objets, d’idées, d’institutions, de pratiques…) entre champs d’influence réciproque. Cette approche transfrontalière est actuellement en vogue. Après l’avoir décrite et située dans son contexte d’émergence, cet article s’en inspire en présentant quelques exemples de flux qui englobent le Québec (au xxe siècle) et la vallée laurentienne (sous le Régime français).

Penser l'Amérique: de l'observation à l'inscription - Vuillemin, Nathalie; Wien, Thomas (Oxford University studies in the Enlightenment, 2017)

Transmission transatlantique de savoirs en sciences naturelles d’Amérique française au XVIIIe siècle; Étude comparative des écrits de Kalm (Canada), de Barrère (Guyane française), de Le Page du Pratz (Louisiane) et de Dumont de Montigny (Louisiane) - Brassard, Alice (Université de Montréal, 2020)
Following their colonization of America in the 17th and 18th centuries, the French drew up inventories for the resources of the occupied or coveted territory. Being able to describe all this wealth, natural history thus became the ultimate colonial knowledge and one of the central cogs of the French Colonial Machine. Also, the textual legacy of this activity is considerable and various points of view are taken into account: an enterprising settler, for example, will not see Louisiana’s resources in the same way as a travelling metropolitan official or a botanist on assignment. However, the colonial perspective is widely spread and all these texts, or almost all of them, are evidence of the appropriation of American plants, minerals and animals. The position of indigenous people and slaves – whether of indigenous or African-American origin – as actors in the process of knowledge creation depends on the context and the author’s stance. This thesis focuses on a small number of compelling texts from the natural history corpus of the French mainland colonies in America. Four authors who worked in or visited Canada (Kalm), French Guiana (Barrère) and Louisiana (Le Page du Pratz and Dumont de Montigny) are studied in depth. We first examine the different contexts of knowledge acquisition. Subsequently, we analyze the colonial resources inventories available at that time and how the sources are managed. Lastly, we conclude by looking at how these naturalist writers transmit to their European readers their newly acquired knowledge and the impact that their work will have.
Keywords: African-American; Afro-Américain; Antoine-Simon Le Page du Pratz (Louisiana); Antoine-Simon Le Page du Pratz (Louisiane); Autochtone; Circulation du savoir; Esclaves; Histoire des sciences naturelles; History - Modern / Histoire - Moderne (UMI : 0582); Indigenous; Jean-François-Benjamin Dumont de Montigny (Louisiana); Jean-François-Benjamin Dumont de Montigny (Louisiane); Knowledge flow; Natchez; Natural science history; Naturalist; Naturaliste; Pehr Kalm (Canada); Pierre Barrère (French Guiana); Pierre Barrère (Guyane française); Slaves; Transatlantic communication; Transmission transatlantique; XVIIIème siècle

La correspondance transatlantique des Prize Papers (1744-1763) : famille, commerce et communications en temps de guerre - Cadieux, Philippe (Université de Montréal, 2016)
Au cours des années comprises entre 1744 et 1763, le monde atlantique connaît deux guerres majeures. La France et ses colonies américaines sont impliquées dans une lutte acharnée contre l’Empire britannique. Les deux puissances rivales misent alors largement sur la guerre de course. Au-delà des conséquences commerciales et militaires évidentes, la guerre de course perturba aussi les communications transatlantiques. En effet, la prise d’un navire signifiait le plus souvent la perte des lettres qu’il transportait ou, dans le meilleur des cas, leur saisie, interrompant du même coup l’acheminement maritime du courrier. Les archives des Prize Papers, conservant des lettres et autres documents saisis par des corsaires britanniques, incarnent bien cette réalité. On y trouve notamment de nombreuses lettres françaises interceptées dans ces circonstances. Considérant que l’intérêt historique de ce fonds d’archives mérite d’être davantage souligné, cette recherche analysera donc certaines de ces correspondances françaises trouvées au sein des Prize Papers. À travers celles-ci, nous tenterons de reconstituer le système de communication transatlantique français et de ses acteurs en temps de guerre. Nous nous pencherons d’abord sur l’histoire de la constitution de ce fonds d’archives bien particulier, avant de présenter les pratiques de communication employées par les correspondants transatlantiques et les façons dont la guerre a pu les affecter. Il sera ensuite question des informations elles-mêmes qui furent véhiculées dans ce contexte si difficile.
Keywords: Atlantique français; Colonial trade; Commerce; Communications transatlantiques; Epistolarity; Famille; Family; French Atlantic; Guerre de course; History - Canadian / Histoire - Canadienne (UMI : 0334); Privateering; Prize Papers; Transatlantic communications; Épistolarité

Les soldats français à Montréal au XVIIIe siècle : activités et intégration sociale des soldats vues à travers les sources judiciaires - Charland, Stéphanie (Université de Montréal, 2006)
Keywords: Histoire militaire; Justice; Montréal; Nouvelle-France; Vie quotidienne; Vie économique; XVIIIe siècle

Les relations diplomatiques franco-autochtones à Montréal, 1701-1713 - Delbreil, Constance (Université de Montréal, 2019)
The Great Peace of Montreal (1701) is a manifestation of the success of French-Amerindian diplomacy, highlighting the many cultural adjustments that allowed for a global alliance and peace between New France and the nations of the Pays d’en Haut. This study looks at the following decade, and the ways in which diplomatic relations between French and Natives developed in Montreal at the beginning of the 18th century. Examining the colonial correspondence that was sent back and forth from Versailles to Montreal, it analyses colonial discourses to better understand how diplomatic practices evolved, and how Montreal played a key role as the urban setting for these pluricultural negotiations. Although these letters present a Eurocentric point of view, a particular consideration was given to Native speeches given during peace negotiations that are transcribed in the correspondence, but also to everything left unsaid by the official correspondents. This study analyses first how diplomacy took place in Montreal, taking an interest in the actors, the urban setting and the practices that surround it. Then it observes the development brought to diplomatic practices by new political stakes in the early 18th century. Ending the analysis at the end of the War of the Spanish Succession (Utrecht, 1713), the thesis concludes that this decade contributed to the continuous strengthening of a pluricultural diplomatic tradition that was ingrained in the urban setting of Montreal.
Keywords: 18th century; Autochtones; Diplomacy; Diplomatie; Diplomats; Histoire urbaine; History - Modern / Histoire - Moderne (UMI : 0582); Montréal; Native Americans; New France; Nouvelle-France; Urban history; XVIIIe siècle

Immigration et agriculture au Canada au XVIIème siècle - Dupin, Laurence (Université de Montréal, 1999)
Keywords: Histoire

Les "Radisson" de l'historiographie revus et corrigés - Guillet, Diane (Université de Montréal, 1998)
Keywords: Histoire

Bougainville, Lévis, Vaudreuil : trajets dans les historiographies de la guerre de Sept Ans - Jalbert, Andréanne (Université de Montréal, 2016)
Very popular since the 1980s, studies on collective memory have stimulated interest in historiography and especially in the construction of heroic figures. The thesis follows this trend in studying how a multinational historiography treated three French officers of the Seven Years’ War’s North American theatre. We observe how Vaudreuil, Bougainville and Lévis have fared at the hands of historians from Great Britain, France, the United States and English and French Canada, from the eighteenth century to the present. The purpose of the study is to isolate the varying perspectives from which historians of different times and national allegiance have examined the three figures. In the end, the three men were seen to incarnate three contrasting, variously interpreted postures. Since historians were particularly sensitive to what they saw as national conflicts, they judged their heroes accordingly. Vaudreuil, the Canadian-born governor of Canada, thus became the champion of his “country”; Bougainville, French-born future navigator and protagonist of the Enlightenment who wrote disparagingly about the colony, was judged on these opinions; while Lévis, a Frenchman who was more discreet in his writings, was evaluated above all as the victor of the battle of Sainte-Foy in 1760.
Keywords: François-Gaston de Lévis; Guerre de Sept Ans; Historiographie; Historiography; History - General / Histoire générale (UMI : 0578); Identités nationales; Louis-Antoine de Bougainville; Memory; Mémoire; National identities; Pierre de Rigaud de Vaudreuil de Cavagnial; Seven Years’ War

Enjeux postcoloniaux et nationaux dans les polémiques entre ethnohistoriens du Pays d’en Haut (1985-2016) - Perreault, Olivier (Université de Montréal, 2020)
This thesis is an exercise in historiography that deals with the ways French, Quebec and US researchers interested in the Pays d’en haut in the seventeenth and eighteenth centuries, have referred, over the past 35 years, to the theme of Native agency. To represent the Native peoples as agents, as they really are, for what they do and not as bit players of a Europeo-centric narrative, this seems to be the rule of the language game ethnohistorian play. However, when we look at the production of the specialists of these Native societies, we rapidly come to the conclusion that the national question and, more broadly, the dynamics of identity inherent to the communities of researchers, still have a considerable impact on these narratives. In order to understand these dynamics, it is useful to develop a historiographic perspective that is rooted in the sociology of science. I will refer more specifically to the works of Bruno Latour and Pierre Bourdieu on controversies among researchers. The idea is to see how researchers, by situating themselves in relation with their peers through alliance, avoidance or opposition, structure an ethnohistorical project. A project that is devoted to knowing better the Native other, but also a project that needs to pass the postcolonial test and hence refers to an area of postcolonial studies that is itself structured through contentions. By seeing how, through the generations, an ethnohistorical model of good practices is constructed and restructured, how collectives of researchers are built, one learns about the world of Native people, but also about the world of the researchers. It is in this perspective that I conduct the analysis of historiographic narratives produced by renowned practitioners of studies on the Pays d’en haut, ethnohistorians who, a few years after having published their main work on the subject, take stock of the situation in regards with Native agency. The historiographic propositions of Bruce Trigger, Richard White and Gilles Havard will allow us to cover the evolution of the field of ethnohistory since 1985.
Keywords: History - Canadian / Histoire - Canadienne (UMI : 0334); Native collective; Pays d’en Haut; agency; agentivité; collectif autochtone; collectif ethnohistorien; contentions among researchers; ethnohistorian collective; historiographie; historiography; polémiques entre chercheurs; sociologie des sciences; sociology of science

Possibilités et limites d'une entreprise seigneuriale : les moulins de Terrebonne, 1720-1775 - DeBlois, Solange (Université de Montréal, 1995)

Marchands voyageurs et équipeurs de Montréal, 1715-1750 - Gagnon, François (Université de Montréal, 1995)

Gérer le patrimoine familial en Nouvelle-France : la famille Boucher et la seigneurie de Boucherville aux XVIIe et XVIIIe siècles - Bouchard, Martin (Université de Montréal, 1994)

Le commerce Montréal-Albany sous le Régime français : histoire d'un phénomène commercial - Guévin, Marc (Université de Montréal, 1995)

Factures et équipements : aspects du commerce des marchandises au Canada 1720-1760 - Daviau, Sébastien (Université de Montréal, 1996)

Les procès-verbaux de vente dans la région de Montréal au XVIIIe siècle : une étude socio-économique - Ducharme, Isabelle (Université de Montréal, 1996)

Profil socioprofessionnel de la noblesse canadienne aux XVIIe et XVIIIe siècles - Major, Éric (Université de Montréal, 1997)

« C’est icy le pays du monde le plus propre a faire des chanvres... si on s’en vouloit donner la peine » : le discours officiel sur le chanvre au Canada, 1660-1840 - Bénard-Saumur, David (Université de Montréal, 2023)
The cultivation of hemp in Canada under the French and British Regimes has long attracted the attention of historians. Until recently, the focus has been on repeated attempts by administrators to develop this culture in Canada. Another element remained largely ignored: the discourse formulated by the colonial authorities on the subject of hemp, an agricultural product as unloved by the Canadian peasantry as it was cherished by the colonial administrators. Whether French or British, the official program, centred on naval supplies (hemp was used in particular for the manufacture of sails and ropes) and associated with mercantilist designs, aimed to replace with Canadian hemp that which successive metropolises import from abroad, mainly from Northern Europe. However, this policy responded only with difficulty to colonial conditions. Despite everything, from Quebec, the colonial administrators, both French and English, persisted for a long time in introducing it, devoting long passages to it in their correspondence with the various ministries in Paris or Versailles, and later in London. By listing the obstacles to hemp culture, they developed a fundamentally stereotyped discourse on the Canadian peasantry, and even on the Creole population in general. These images will have a long life, surviving then change of regime at the Conquest and influencing both contemporary authors and the historical narratives that would be produced until the middle of the 20th century. Nevertheless, there was a learning process. It manifested itself in two stages: in the more lucid formulations of the administrators of the late French Regime and, nearly half a century later, in the agronomic discourse emerging in the vicinity of the Colonial Assembly, more sensitive to the possibilities of local agriculture.
Keywords: =CL; Ancien Régime; Bas-Canada; Canada; Canadian history / Histoire du Canada (UMI : 0334); English regime; French regime; Haut-Canada; Lower Canada; New France; Nouvelle-France; Province de Québec; Province of Quebec; Régime anglais; Régime français; Upper Canada; agriculteurs; colonie; colony; culture du chanvre; discours; discourse; farmers; gouverneurs; governors; habitants; hemp cultivation; inhabitants; intendants; representations; représentations

Convertir des âmes et des castors : rivalités missionnaires et accusations commerciales en Nouvelle-France au XVIIe siècle - Dupont-Germain, Arnaud (Université de Montréal, 2023)
This thesis explores the rivalries between Jesuit, Recollect and Sulpician missionaries in the 17th century in New France. Specifically, it examines the polemical discourse about the missionaries, whether it came from religious competitors or from members of the colonial administration. Although these missionaries were all part of a common apostolic project, the sources reveal that different networks were struggling at the time so that some missionaries could enjoy a monopoly over the souls of the colony, while others were relegated to the background. In this nascent Church, several disagreements that raged between these three religious families can help to explain the tensions that we find in their writings. The main issues were the francization of the First Nations and the founding of the bishopric of Quebec. Furthermore, the rivalries between the Jesuits, the Recollects and the Sulpicians went far beyond the spiritual framework and regularly led to commercial issues. Certain missionaries, the Jesuits in particular, were accused throughout the century by various actors of enriching themselves in various ways, and of engaging in the fur trade. Rather than focusing on the veracity of these attacks, this thesis proposes to analyze them and to try to understand their origin and function. These accusations must also be put in relation to the rivalries that the missionaries had to face in their other missions during the same period.
Keywords: 17th century; =CL; Canadian history / Histoire du Canada (UMI : 0334); Jesuits; Jésuites; New France; Nouvelle-France; Recollects; Récollets; Sulpicians; Sulpiciens; XVIIe siècle; fur trade; missionaries; missionnaires; polemic; polémique; rivalités; rivalries; traite des fourrures

« Nous bumes a ta santé » : la correspondance transatlantique à travers les lettres reçues par Louis-Guillaume Verrier, magistrat à Québec (1728-1758) - Labonté, Marc-Antoine (Université de Montréal, 2021)
Communications between France and Canada, in the 18th century, were defined by an annual rhythm marked by the seasons and the dangers of crossing the Atlantic. Louis-Guillaume Verrier was the king’s attorney-general at the Conseil supérieur of Québec between 1728 and 1758. Born in France, he moved to Québec to join the Conseil supérieur at the age of 37. He left us around 200 letters that he received during those 30 years. By reading these documents, we understand the importance of a good organization to make sure that the letters reach their addressee efficiently. All kinds of people write to Verrier, from close members of his family to mere acquaintances who wish to obtain services for a relative in New France. Family and friends of the attorney-general send news of their health and hope that their addressee’s is good too. Verrier also receives a lot of news concerning European politics and administrative or judiciary matters. This reflects (indirectly) Verrier’s desire to be kept informed of what goes on in the world that he left behind, pointing to his attachment to his motherland and the people that he no longer saw, but also a desire to return someday to continue his career. Living in an Atlantic world, Louis-Guillaume Verrier belongs at the same time to Canada, where he lives, and to France, where his relatives’ letters take him each year.
Keywords: 18th century; Atlantique français; Canada; Communications transatlantiques; Conseil supérieur; Epistolarity; French Atlantic; History - Canadian / Histoire - Canadienne (UMI : 0334); Louis-Guillaume Verrier; New France; Nouvelle-France; Québec; Supreme Council; Transatlantic communications; XVIIIe siècle

Ce qui échappe à la Raison d'État : stratégies discursives des intendants de la Nouvelle France confrontés à la contrebande des fourrures, 1715-1750 - Roy, Gilles L. (Université de Montréal, 2019)
In New France in the eighteenth century, illicit trade between Montreal and Albany had become commonplace. The economic structures of the colony and the repressive measures aimed at contraband gave this trade its particular organization. Another important factor in the normalization of illicit trade was the discourse produced by colonial authorities on contraband. As top magistrate and administrator of the colony, the intendant of New France occupied a singular place in the repressive and discursive apparatus set up to fight unauthorized trade. The intendant and his Montreal subdélégué brought smugglers to trial, and the intendant often took up the matter in his correspondence with his superior in metropolitan France, the secretary of state of the Marine. In this thesis, three intendants will bring their own unique brand of discourse to bear on the Montreal-Albany trade. Based on information obtained from first-hand reports, these intendants classify facts and behaviours related to contraband, for judicial proceedings and ministerial decision-making. But the means and methods they employ to defend the fur exporting privilege of the Compagnie des Indes prove to be rather deficient and counterproductive. As their discourse delineates the many obstacles to the full application of French colonial law, the intendants give the Montreal-Albany trade its colouring. In official correspondence, the intendant describes the consolidated network of merchants who hold intercolonial commerce in their grasp, and the deleterious effects of distance on colonial subjects from the civilizing ways of the metropole. The intendant scrutinizes how the Compagnie's policies stimulate the phenomenon it deplores and anticipates breaches to colonial security related to the participation of the Domiciliés, or "settled" Natives, in the prohibited trade. This study focuses on the discursive strategies of three intendants, Michel Bégon de La Picardière (1712-1726), Claude-Thomas Dupuy (1726-1728), and Gilles Hocquart (1728-1748), who formulate in their correspondence with the secretary of state of the Marine in France matters of official policy toward a contraband which they officially must fight, but also tolerate.
Keywords: Albany; Amérindiens; Ancien Régime; Domiciliés; First Nations; History - Canadian / Histoire - Canadienne (UMI : 0334); Montreal; Montréal; New France; Nouvelle France; Settled Natives; colonie; colony; contraband; contrebande; discours; discourse; fur trade; justice; marchands; merchants; traite des fourrures

Du pont du baleinier aux laboratoires du Muséum : circulation des objets et savoirs marins à la fin du XVIIIe siècle en France - Stantina, Céline M. (Université de Montréal, 2019)
Examining a specific publication, l’Histoire naturelle des Cétacées (1804), this study seeks to determine how Lacépède managed to compose his classic work of cetology without having seen a single whale in his entire life. The operating hypothesis is that, while referencing numerous well-read naturalists’ and other authors’ works, Lacépède was in fact exploiting the knowledge held by the persons that were the most familiar with the species: the whalers. Since this vernacular maritime knowledge does not appear clearly in the book, we will investigate the naturalist’s methods, sources and relationships with other fellow natural philosophers of the Museum d’histoire naturelle to try to understand the role seamen could have played in this work. To help us examine the complex mechanisms of the circulation of natural knowledge, we will benefit from a bibliography mostly composed with research on the Atlantic world, highly comprehensive on these topics. We will carefully take into consideration the political, scientific and cultural context of early nineteenth century France.
Keywords: Atlantic; Atlantique; Baleine; Cetology; Curiosity; Curiosité; Cétologie; Histoire des sciences; Histoire naturelle; History - Modern / Histoire - Moderne (UMI : 0582); Knowledge; Lacépède; Museum; Muséum; Savoir; Science; Whales; Whaling

Histoire : 75 ans - Comité du 75e anniversaire du Département d'histoire; Wien, Thomas (2023)

Entre deux régimes : Louis-Léonard Aumasson de Courville et ses Mémoires - D'Amours, Marc-André (Université de Montréal, 2017)
Publiés en 1838 mais datant pour l’essentiel de la fin du régime français au Canada, Les Mémoires du S... de C..., contenant l’histoire du Canada durant la guerre, et sous le gouvernement anglais sont attribués depuis 1940 à Louis-Léonard Aumasson de Courville (c. 1722-1781), un notaire et écrivain d’origine champenoise ayant vécu en Acadie française et dans la vallée du Saint-Laurent.. Le manuscrit (conservé aux archives du musée McCord de Montréal) à la base de cette publication daterait donc de la fin des années 1750. Peu après la prise de la colonie par les Britanniques, Courville s’est mis à réviser ce texte à l’intention de la nouvelle administration, rédigeant un deuxième manuscrit correspondant, à se fier à l’exemplaire conservé (également aux archives McCord), à une partie seulement du premier. Les deux versions se distinguent de nombre d’autres témoignages de cette période par leur ton incisif et leur touche anticléricale. Le premier chapitre du mémoire s’attache à suivre l’histoire des textes courvilliens : les circonstances de leur rédaction et leur utilisation dans l’historiographie, mais aussi leur étude par Aegidius Fauteux, celui qui percera le mystère entourant la personne qui s’est cachée pendant presque deux siècles derrière le pseudonyme du « S... de C... ». Le deuxième chapitre s’interroge sur les motifs de l’auteur de ces mémoires, s’attachant pour ce faire à suivre son parcours personnel difficile. Enfin, le troisième chapitre est consacré à l’analyse du propos de Courville dans les deux versions de ses Mémoires, véritable réquisitoire contre la corruption du régime français finissant.
Keywords: Aegidius Fauteux; French regime; History - Canadian / Histoire - Canadienne (UMI : 0334); Louis-Léonard Aumasson de Courville; anticlericalism; anticléricalisme; corruption; indictment; memory; mémoire; régime français; réquisitoire

Jacques Rousseau, une voie de l’ethnohistoire canadienne-française : prédécesseurs, contextes et production - Lavergne, Rafael (Université de Montréal, 2025)
Ce mémoire de maîtrise se penche sur la figure de Jacques Rousseau (1905-1970), un chercheur prolifique dont la longue carrière transdisciplinaire l'a mené de la botanique à l’ethnohistoire. Bien qu’il ait été, de son vivant, une personnalité publique et un scientifique de renom, son œuvre autochtoniste est en grande partie tombée dans l'oubli historiographique. Cette recherche vise ainsi à questionner sa place dans la généalogie de l’ethnohistoire et à analyser la nature singulière de son travail. Le parcours de Rousseau, qu'il soit institutionnel ou personnel, a été déterminant dans l'évolution de ses recherches. De son rôle de bras droit du frère Marie-Victorin, au Laboratoire et au Jardin botanique de Montréal, à ses postes prestigieux de professeur invité à la Sorbonne et de chercheur au Centre d’études nordiques de l’Université Laval, ses nombreuses explorations dans le Nord-du-Québec ont agi comme un véritable moteur de sa production intellectuelle. C’est à travers ses contacts directs et répétés avec les peuples autochtones — notamment ses guides innus, mais aussi les Naskapis et les Abénaquis — que son intérêt pour leurs modes de vie, leurs histoires et leurs cultures a progressivement évolué. La thèse centrale de ce mémoire est que l’œuvre de Jacques Rousseau mérite une réévaluation. Elle constitue une approche de l'ethnohistoire tout à fait singulière, ancrée dans une démarche pragmatique et un engagement sur le terrain. L’étude de son travail d’intellectuel polymathe permettra de décortiquer la manière dont il a su mobiliser sa notoriété pour rendre l’histoire autochtone plus accessible au grand public. Elle mettra également en lumière la profonde évolution de sa pensée, qui est passée d'une vision initiale d'intégration coloniale à une critique explicite des politiques du colonialisme interne de son époque.
Keywords: _AV

L’imaginaire évolutionniste dans les Mémoires de la Société royale du Canada (1882-1894) - Cadieux, David (Université de Montréal, 2018)
Ce mémoire explore la place de l’évolutionnisme culturel dans les premières années d’existence de la Société royale du Canada. Il représente une contribution à l’histoire culturelle et sociale du monde intellectuel canadien. La recherche est basée sur une analyse des communications traitant de la question autochtone présentées dans les Mémoires entre 1882 et 1894. La période couverte recoupe une partie des années durant lesquelles le gouvernement canadien développe et applique une politique de colonisation dans l’ouest du pays. Cette histoire de la production de la Société royale du Canada offre une perspective originale sur l’histoire scientifique du pays et illustre le rôle de l’institution dans l’élaboration de certains discours racisés. Les publications révèlent en particulier l’importance de l’anthropologie linguistique dans la diffusion du paradigme évolutionniste. Cette étude présente les indices du développement de ce paradigme à travers certaines interactions entre les membres de la Société royale du Canada. L’adhésion à la rhétorique évolutionniste est manifeste dans les textes consacrés aux Autochtones parus dans les Mémoires, particulièrement à travers la manipulation de théories linguistiques qui produit des classifications hiérarchiques.
Keywords: Anthropologie; Anthropology; Autochtones; Evolutionism; History - Canadian / Histoire - Canadienne (UMI : 0334); Linguistique; Native Canadians; Paradigme; Royal Society of Canada; Société royale du Canada; linguistics; paradigm; Évolutionnisme

La transmission du patrimoine seigneurial des familles du gouvernement de Montréal aux XVIIe et XVIIIe siècles - Couvrette, Sébastien (Université de Montréal, 2003)
Keywords: Histoire

Dynamiques de pouvoir, genre et rituels autochtones dans les écrits des jésuites en Nouvelle-France, 1632-1724 - Danis, Ariane (Université de Montréal, 2020)
This thesis presents representations of the traditional ritual practices of the Iroquoians and Algonquians that the French Jesuit missionaries have revealed in their writings. Sometimes in spite of themselves, the missionaries describe Indigenous people endowed with religious powers, descriptions which we will examine. The territory analyzed is therefore mainly that of the missions, namely the St. Lawrence Valley, the surrounding country and the Great Lakes region, a slice of America that remained largely Indigenous during the period of interest to us, namely from 1632, date of the first Relations with the Jesuit Paul Le Jeune, until 1724, the date of publication of the book Mœurs des Sauvages by Joseph-François Lafitau. This careful examination of the Jesuit works reveals, from a perspective of gender history, excerpts relating to rituals and spheres of activity of Aboriginal men and women. These results are confronted with numerous studies on First Nations or on the Jesuits and their North American missions. This multidisciplinary convergence then leads us to ask: what do missionaries see, or do not see, in the role of men, women, and to some extent, “men-women” and “women-men” within Aboriginal rituals, and in what circumstances?
Keywords: Algonquians; Algonquiens; First Nations; History - Canadian / Histoire - Canadienne (UMI : 0334); Iroquoians; Iroquoiens; Jesuit missions; Jésuites; Premières Nations; genders; genres; representations; représentations et symboliques; rituality; rituels; symbolic

Subdélégués et subdélégations dans l'espace atlantique français : étude comparative des intendances de Caen, Lille, Rennes, Fort-Royal et Québec (fin XVIIe - fin XVIIIe siècle) - Didier, Sébastien (Université de Montréal, 2020)
Subdelegates of the intendancies indirectly served the king of France at the local level. The study of their institution in five intendancies offers an original point of view on the Ancien Regime state and its administration. Subdelegations existed in all the provinces of the kingdom: in those known as pays d’élections, pays d’États or pays d’imposition, as well as in the colonies. Studying them makes it possible to question this typology and especially the centralization of the Kingdom of France. By comparative prosopography, 687 subdelegates in the 159 subdelegations of the intendancies of Caen in Lower Normandy, Fort-Royal in the Lesser Antilles, Lille in Flanders, Quebec in Canada and Rennes in Brittany are studied. This method allows for inter-provincial and transatlantic as well as intra-provincial comparisons and a multiscalar analysis of the royal administration. Subdelegations emerge as institutions of intendancy, in the service of the monarchy and exercised by local notables. Taxation, civil justice or administrative litigation, investigations, surveys and statistics, royal militia and corvée, public contracts, epidemics and assistance, supervision of municipalities, many powers concern them. In practice, they varied between provinces and between subdelegations. Everywhere, magistrates, mayors, marine commissioners or other notables served as subdelegates. Between bureaucracy and patronage, they participated in a limited administrative centralization. Subdelegations mainly generated multiple mediations of royal power, transforming it through provincial variations and local translations.
Keywords: History - Modern / Histoire - Moderne (UMI : 0582); administration; intendant; mediation; multi-scale; multiscalaire; médiation; notability; notabilité; prosopographie; prosopography

La représentation des pionniers et des pionnières dans les récits sur les origines nationales au Canada français - Fortin, Marie (Université de Montréal, 2012)
La figure des « pionniers » et des « pionnières » est devenue un référent culturel identitaire fondamental dans le développement de la mémoire collective québécoise. Nous montrons que ces objets culturels s’intègrent et participent à la représentation identitaire imaginée et conçue à l’intérieur d’un discours visant à affirmer une identité fondée en bonne partie sur l’histoire des Canadiens issus de l’immigration française du XVIIe siècle. La conjoncture politique du XIXe siècle favorise l’émergence d’un récit patriotique et d’un discours nationaliste conservateur, tissés par certains auteurs et appuyés par les élites politiques et les membres du clergé. Ces discours ont contribué à construire la nation canadienne et à l’inscrire dans un passé lointain et glorieux - dans l’imaginaire des « civilisations ». Dans cette perspective, l’objet culturel « pionnier » et l’objet culturel « filles du roi » sont mobilisés avec force dans la construction du passé magnifié de la nation canadienne. Nous nous intéresserons donc à la construction de l’image de ces deux figures pionnières dans les récits sur les origines nationales, ainsi qu’à leur utilisation dans le développement d’un sentiment identitaire canadien-français.
Keywords: History - Canadian / Histoire - Canadienne (UMI : 0334); King’s Daughters; New France; Nouvelle-France; filles du roi; imaginaire; imagination; narrative; nation; pioneer; pionnier; pionnière; récit

Le monde de Jean Alexis Lemoine dit Monière, marchand de Montréal au XVIIIe siècle - Gousse, Suzanne (Université de Montréal, 2020)
From the 1950s to the 1970s, historians’ attention was turned towards the disappearance of a bourgeoisie canadienne which should have made the transition from commercial to industrial capitalism. These studies began, so to speak, with the end, in attempting to define the long-term historical consequences of the Conquest on an as-yet ill-defined group that in principle included some merchants. This thesis follows new investigations in both Europe and the USA which have permitted to look anew, often with a cultural history approach, at merchants of the Early Modern period. Focusing on a Montreal merchant outfitter (marchand équipeur) and his family, the investigation first seeks to determine if the Canadian merchants’ culture (broadly defined) was similar to that of their French counterparts who worked on the same business level. A second aim is to evaluate the leeway available to individuals in face of the general conditions of the trade and the role of networks in the merchants’ career. Finally, the thesis attempts to define the self-conception of these men while looking at their lifestyle and the various roles they played in their community. To complete such a study, we have chosen to look « wide and deep » like micro-historians have before us. The study examines the long life of the équipeur, Jean Alexis Lemoine dit Monière, who chose to settle in Montreal in 1715 and whose career Louise Dechêne had followed until 1725. After her, historians have since pictured Monière as a typical marchand équipeur. But he might not have been typical, he might even have been a « limiting case ». The thesis follows him to the end of his life and looking for all the opportunities that were offered to him along the way. It accords considerable importance to the material and immaterial legacy of his father, Jean Lemoine, and to what Monière passed on to this son, Pierre Alexis and a few nephews. Situating Monière between his father who emigrated from Rouen, his brothers and his own son, permits us to see the emergence of a profession, that of équipeur. We look at how Monière, who died in 1754, was prepared to embrace the merchant’s profession and how he perceived the way he should work as an équipeur. This study affords a better understanding of merchants’ culture, broadly conceived, in early French Canada. Exploring a variety of sources and using a micro-historical approach, we hope to have followed Dale Miquelon’s suggestion to look (again) at the merchants’ world with the eyes of the people of the times in order to answer today’s questions.
Keywords: 17th century; 18th century; Canada préindustriel; Commerce; Conquest; Conquête; Culture; Fur trade; Guerre de Sept Ans; History - Canadian / Histoire - Canadienne (UMI : 0334); Marchands; Merchants; New France; Nouvelle-France; Négociants; Seven Years War; Traite des fourrures; Wholesalers; XVIIIe siècle; XVIIe siècle

Passer outre la barrière culturelle : comment les Britanniques se renseignent sur les populations du Canada et de l’Inde, 1757-1774 - Gervais, Émy (Université de Montréal, 2020)
This study compares methods of information gathering in two territories that became part of the British Empire after the Seven Years’ War. We bring these two extremely different regions into the same frame by asking: how did the British gather information about the populations of Canada and Bengal? Our study is part of several historiographical currents that offer a rereading of the history of Great Britain and its colonies, which is the subject of our first chapter. In the next chapter, we explore the post-conquest era in Canada. After the conquest of this territory (1759-1760), British authorities faced the task of administering the Canadian population. At first, they tried to implement a new governmental regime deemed suitable for the Canadian context. However, since the majority of the population they governed was of different religious denomination (Catholics) and of French origin, they had to modify the regime ten years later. In the third chapter, we look at the British presence in Bengal after the battle of Plassey in 1757. The British, through the East India Company, acquired a certain influence over local authorities, which allowed them to govern indirectly via the Mogul Empire’s governors, the nabobs. Nevertheless, cultural differences were much more significant than with the Canadian population of European origin: the Mogul Empire was a Muslim polity, with a Persian administration, and much of the population was Hindu. From our reading of the official correspondence, between the colonial administrators and the metropolitan government in the first case, and between the agents of the company and its directors in the second, we affirm that in both situations the British tried to gather more information. However, important institutional and cultural differences distinguish the types of information sought as well as the approaches to collecting information. The results of our research ultimately converge on one point: the search for information passed through a whole range of local intermediaries. In the last chapter, after having explored the “information order” implemented or adapted by the British in each colonial context, the study considers how colonial information was received and shaped by the metropolitan authorities. To this end, the efforts of officials and parliamentarians to learn about colonial conditions during the drafting of two laws, the Quebec Act (1774) and the Regulating Act (1773) are highlighted through a reading of the Parliamentary debates. Here also, many differences are visible. To become informed about Canada, British authorities relied heavily on the help of the colonial administrators who stayed in Canada after the regime change. However, in the Indian case, they depended mostly on documentary sources, namely the books of the EIC.
Keywords: Bengal; Bengale; British empire; Canada; Colonial intelligence; Empire britannique; History - Modern / Histoire - Moderne (UMI : 0582); Inde; India; Information; circulation de l'information; colonialism; colonisation; flow of information; information coloniale

Les capitaines des troupes de la Marine de 1683 à 1739 : la carrière militaire en Nouvelle-France - Lalancette, Louis (Université de Montréal, 2016)
In 1683, the French monarchy decided to send three companies of infantry of the Marine to quell the Iroquois, who were waging war against the colony that was then under Marine jurisdiction. Unable to put an end to the threat, the king sent more companies whose officers had Marine or infantry experience. The war, now extended to the British colonies forced the Marine to station troops permanently in Canada. They called by the administrators : troupes de la Marine. Another sign that this colonial army had become permanent is the opening of the officer corps to the local nobility. A few decades later, the officier corps nearly entirely consisted of Canadian noblemen. Some of the officers, most of them born in Canada, have been the subject of biographies. Some historians have studied the military noblesse as a social group. The military career of the officers of the troupes de la Marine has not, however, been studied has a whole. The captains, that is, the men who reached the top of the hierarchy of the troupes de la Marine before 1739, are the subject of this analysis. The study examines the main stages of their colonial military experience, while taking into account the officers birthplace, so as to highlight certain trends of Ancien-Regime society.
Keywords: ANCIEN REGIME; ANCIEN RÉGIME; CAPITAINES; CAPTAINS; CARRIÈRE MILITAIRE; COMPAGNIES FRANCHES DE LA MARINE; History - Military / Histoire - Militaire (UMI : 0722); MILITARY CAREER; NEW-FRANCE; NOUVELLE-FRANCE; OFFICERS; OFFICIERS; TROUPES DE LA MARINE

L'histoire "culturelle" dans la Revue historique - Philippon, Martin (Université de Montréal, 2004)
Keywords: Civilisation; Culture; Histoire culturelle; Historiographie; Revue historique; École méthodique

Tanneurs et tanneries dans le gouvernement de Montréal au XVIIIe siècle - Perrier, Jocelyne (Université de Montréal, 2002)
Keywords: Artisans; Canada; Cuir; Histoire sociale; Préindustriel; Québec; Technique

Régime d'historicité et historiographie en France et au Québec, 1956-1975. Michel de Certeau, Fernand Dumont et François Furet - Poitras, Daniel (Université de Montréal, 2015)
L’historien n’écrit pas de nulle part. Ancré dans son présent et participant à la société, il en épouse – ou critique – les projets, les utopies et les grands récits. Nous proposons dans ce travail d’approfondir cet ancrage à travers une histoire croisée et comparée des expériences du temps de deux historiens français (Michel de Certeau, François Furet) et d’un historien-sociologue québécois (Fernand Dumont). Notre objectif est double : il s’agit d’établir, dans un premier temps, les correspondances entre leurs expériences lors de deux tournants, celui des années 1960 et celui des années 1970. Tout en prenant en compte les contextes des auteurs à l’étude, nous élargirons l’échelle d’analyse afin de cerner la contemporanéité d’expériences du temps qui ne se réduisent pas aux seuls cadres nationaux. Nous pourrons ainsi établir les coordonnées des régimes d’historicité à chaque tournant en contribuant à préciser les différentes combinaisons des modes futuristes et présentistes en jeu. Dans un deuxième temps, nous explorerons les liens entre historiographie et régime d’historicité afin de mettre en évidence les jonctions entre les considérations épistémologiques et l’horizon d’attente des historiens à l’étude. En abordant plus spécifiquement la question du rôle de l’historien dans sa société, nous jaugeons les transformations parallèles de son expérience du temps et de ses pratiques historiographiques. Le passage de l’expérience d’une Histoire en marche au tournant de 1960 à celle d’une histoire bloquée au tournant de 1970 affecte considérablement la place et le statut de l’historien. D’éminent passeur du temps à l’écoute du sens du progrès, l’historien voit son statut contesté et marginalisé, ce qui ne veut pas dire que son rôle est moins important. Qu’il débusque des alternatives passées ou court-circuite des téléologies, il est chargé de maintenir coûte que coûte ouverts les horizons du temps. Nous verrons spécifiquement le sens que prenait cette tâche à un moment où la possibilité d’une « société nouvelle », après Mai 68, pointait à l’horizon des contemporains.
Keywords: Experience of time; Expérience du temps; France; Histoire croisée; Historiographie; Historiography; History - General / Histoire générale (UMI : 0578); Québec; Régime d'historicité

Histoire sociale et annales ESC : territoires, pratiques et discours - Poitras, Daniel (Université de Montréal, 2005)
Keywords: Annales; Discours; France; Histoire des mentalités; Histoire sociale; Historiographie; XXe siècle; esprit du temps

La mise en nourrice en Nouvelle-France : l'île de Montréal, 1680-1768 - Robert, Emilie (Université de Montréal, 2012)
Les médecins et autres écrivains de l’Ancien Régime qui ont décrié les effets néfastes de la mise en nourrice l’ont tenue en partie responsable de la forte mortalité infantile. L’habitude de confier l’allaitement et les soins de l’enfant à une femme autre que sa mère est présente dès le XIIIe siècle dans les milieux aristocratiques français. Bourgeois et autres citadins feront de même dès le XVIIe siècle. Transportée outre-Atlantique par les colons du Canada, la mise en nourrice a laissé de nombreuses traces dans les sources paroissiales, notariales et judiciaires de la colonie. Les démographes et historiens se sont penchés sur le phénomène dans le cadre d’études portant sur différents groupes sociaux (noblesse, « bourgeoisie ») ou populations (ville de Québec et l’ensemble du Canada sous le Régime français). Ils ont privilégié l’étude des nourrissons et de leurs familles. Ce mémoire s’intéresse à la mise en nourrice à Montréal et aux alentours des années 1680 aux années 1760. Il s’emploie d’abord à suivre le parcours de 436 nourrissons, décédés pour la plupart en bas âge : milieu socio-professionnel des parents connus, profil démographique, lieu d’accueil par une nourrice. Il étudie ensuite 245 femmes qui ont pris soin de ces enfants : leur parcours migratoire, les différents paramètres socio-démographiques de leur existence. Plusieurs de nos observations correspondent à celles d’autres chercheurs ou, du moins, ne les contredisent pas, tout en offrant une perspective montréalaise sur le phénomène. Au chapitre de l’inédit, citons l’élargissement, au XVIIIe siècle, de la gamme des professions exercées par les pères de nourrissons, ainsi que l’existence de plus d’un profil de nourrice, du point de vue de l’âge (et de la capacité à allaiter), de l’état matrimonial et du degré de vulnérabilité.
Keywords: Childhood; Enfance; Famille; Family; Feeding Techniques; Femmes; Histoire; History; History - Canadian / Histoire - Canadienne (UMI : 0334); Infant Mortality; Maternité; Mise en nourrice; Montreal; Montréal; Mortalité infantile; Motherhood; New France; Nouvelle-France; Techniques d'alimentation; Wet-Nursing; Women

"La mauvaise herbe" : familles turbulentes à Montréal au XVIIIe siècle - Villeneuve, Nathalie (Université de Montréal, 2005)
Keywords: Histoire de la criminalité; Histoire de la famille; Histoire du genre; Marginalité; Nouvelle-France

Les membres de la Compagnie des Cent-Associés : étude d'histoire sociale - Beaudin, René (Université de Montréal, 1997)
Ce mémoire s'intéresse aux 202 individus qui ont été actionnaires de la Compagnie des Cent-Associés au cours des 35 années d'existence de l'entreprise. En étudiant la dynamique sociale qui s'opère à l'intérieur de ce groupe bien défini, nous cherchons à appréhender un peu plus la société française d'Ancien Régime. Dans un premier temps, nous établissons le contexte difficile dans lequel ces gens ont évolué en soulignant les éléments de la macro et de la microconjoncture qui ont pu les affecter, tant sur les plans économiques, politiques que sociaux. Dans le second chapitre, nous présentons tout d'abord les sources et la méthode qui nous ont permis, par la suite, d'établir le profil social des associés à travers une répartition sociale et chronologique qui tenait compte de leur appartenance à un ordre et à un corps, de même que de leurs lieux de résidence, de leurs propriétés foncières, de leur participation dans la Compagnie et, enfin, de leur expérience coloniale. Dans le dernier chapitre, nous nous attardons plus à la dynamique sociale en examinant d'autres liens de solidarités, tels les liens familiaux et les liens d'affaires, et en analysant des sous-groupes particuliers tels que les sept fondateurs, les 22 directeurs et les 12 acquéreurs de lettres de noblesse de la Compagnie. Il ressort donc de cette étude que les membres de la Compagnie des Cent-Associés sont surtout des Français du nord et de l'ouest qui se situent socialement à la frontière entre la noblesse et le tiers état et qui appartiennent majoritairement au monde du négoce, de l'office et de la finance. La dynamique sociale de ce milieu se manifeste, avec plus d'évidence, à travers les solidarités de corps et de lieux et, plus discrètement, à travers les solidarités de lignages, de fidélités et d'ordres. Ainsi, la composition sociale de l'entreprise et la dynamique qui l'accompagne font que la Compagnie des Cent-Associés s'inscrit bien dans la mouvance de la montée bourgeoise, en France, au XVIIe siècle.
Keywords: =CL

Les boulangers de Montréal, de la fondation à 1750 : étude d'histoire socio-économique - Lamonde, Robert (Université de Montréal, 1997)

Les familles de tisserands de la plaine de Montréal au XVIIIe siècle : étude socioprofessionnelle - Roy, Emmanuelle (Université de Montréal, 1997)

Histoire véritable et naturelle de la Nouvelle-France - Boucher, Pierre (Almanach, 2014)

Iberville et les historiens : Le parcours historiographique d'un héros de la Nouvelle-France - Camirand, David (Université de Montréal, 2007)
Keywords: Historiographie (Québec); Mémoire collective; Pierre Le Moyne d'Iberville (1661-1706)

Les couturières en Nouvelle-France : leur contribution socioéconomique à une société coloniale d'Ancien Régime - Gousse, Suzanne (Université de Montréal, 2009)
Keywords: 18th century; Artisans; Colonies françaises; Femmes; French colonies; Fur trade; Histoire sociale; Montreal; Montréal; Social history; Traite des fourrures; Women; XVIIIe siècle

Être médecin du roi en Nouvelle-France : le cas de Michel Sarrazin - Gauthier, Jean-Richard (Université de Montréal, 2001)
Keywords: 1659-1734; =CL; Michel; Sarrazin

La rationalité paysanne dans le Québec préindustriel : une approche historiographique - Laramée, Marc-André (Université de Montréal, 2015)
La question de la rationalité socioéconomique propre aux paysans canadiens-français occupe dans l'historiographie canadienne du Québec rural préindustriel une place de choix, ayant été invoquée tour à tour pour glorifier ou condamner une population aux pratiques jugées à bien des égards différentes de celles des société anglo-saxonnes nord-américaines. Néanmoins, aussi importante soit-elle, cette problématique a rarement été abordée de front par les historiens, qui ont plutôt choisi de l'inclure en filigrane d'interprétations plus ciblées de réalités connexes. Dans cette optique, nous nous proposions dans ce mémoire de dégager, par le biais de l'analyse critique d'un échantillon de productions historiques représentatives des courants plus généraux dont elles sont issues, les principales représentations de la rationalité socioéconomique paysanne véhiculées par les historiens canadiens (tant francophones qu'anglophones) depuis 1960, de les expliquer à la lumière des particularités des contextes dans lesquels elles ont été produites ainsi que d'en retracer le parcours historiographique. Cette démarche nous a permis de constater clairement l'existence de trois paradigmes interprétatifs ayant successivement dominé le discours historique sur la question depuis 1960. Cette évolution, si elle s'accorde bel et bien au rythme du progrès méthodologique de la science historique, présente toutefois plusieurs originalités fermement ancrées dans les particularités du contexte dans lequel elle s'est déroulée, dont les principales sont la question nationale, la dichotomie ethnolinguistique de l'historiographie canadienne et la portée sociale significative des interprétations proposées.
Keywords: Historiographie; History - Canadian / Histoire - Canadienne (UMI : 0334); Québec périndustriel; historiography; mentality; mentalité; paysannerie; peasantry; preindustrial Quebec; rapports sociaux; rationality; rationalité; rural economy; social relations; économie rurale

«Et ferez justice» : le métier d’intendant au Canada et dans les généralités de Bretagne et de Tours au 18e siècle (1700-1750) - Ouellet, Marie-Eve (Université de Montréal, 2015)
Cette thèse consiste en une étude comparative du métier d’intendant au Canada et dans les généralités de Bretagne et de Tours dans la première moitié du 18e siècle (1700-1750). Elle s’appuie sur l’intendant pour s’interroger sur l’existence de spécificités dans l’exercice du pouvoir en contexte colonial par rapport au contexte métropolitain. Considéré par la plupart des historiens de la France d’Ancien Régime comme le personnage clé de l’évolution politique qui aurait fait passer la monarchie de sa phase judiciaire jusqu’à sa phase dite « administrative », l’intendant de justice, police et finance ou commissaire départi est au coeur des débats sur l’absolutisme et son rôle de première ligne dans l’oeuvre de centralisation monarchique en fait le sujet idéal pour observer la portée réelle de ce régime sur le terrain. L’examen du fonctionnement de l’intendance est un préalable obligé pour qui veut comprendre les rapports entre administrateurs et administrés et mieux cerner la capacité de régulation de l’État. Dans le cadre des attributions définies par sa commission, quelles sont les tâches qui l’occupent concrètement ? Cette thèse s’intéresse à l’intendant du point de vue de sa pratique, en s’appuyant sur la description interne des sources produites par l’intendant pour décortiquer ses mécanismes d’intervention. Deux types de documents sont analysés successivement, soit la correspondance, incluant les pièces jointes et les documents de travail, et les actes de portée réglementaire, incluant les ordonnances et les arrêts du Conseil d’État. Chemin faisant, nous avons fait la rencontre des individus et groupes qui sollicitent l’intervention de l’intendant, levant le voile sur les rapports de pouvoir et les interactions qui le lient à ses supérieurs, aux justiciables et aux institutions locales. L’exercice permet de poser en des termes nouveaux l’action de ce personnage dont on connaissait les attributions et principales décisions, mais beaucoup moins leur logique sous-jacente.
Keywords: Administration; Bretagne; Canada; Finance; History - Canadian / Histoire - Canadienne (UMI : 0334); Intendant; Justice; New France; Nouvelle-France; Ordinance; Ordonnance; Police; Tours

La criminalité soldatesque au Canada sous le Régime français - Ste-Marie, Philippe (Université de Montréal, 2020)
Since the arrival of social history in the 1960s, the military history of Canada under the French Regime has been enriched by several studies of soldiers. Historians of justice have also investigated the rank and file as a social group. These studies – which were not exclusively devoted to soldiers – adopted a quantitative approach. Though historians have viewed various aspects of soldiers’ lives, none have singled out criminality. That is precisely what this thesis attempts to do, by exploiting principally the judicial archives. More precisely, it analyzes criminal trials involving soldiers, relying as well on Ancien Regime jurisprudence to help place soldiers’ criminality in perspective. The trials offer a view of the different forms of this criminality and of some of the contributing factors. Lastly, several trials in addition to the colonial correspondence show that the army, not just a war machine, also played role in the rehabilitation of soldiers inclined to criminal behavior.
Keywords: History - Canadian / Histoire - Canadienne (UMI : 0334); New France; Nouvelle-France; criminality; criminalité; indubordination; insecurity; précarité; soldat; soldier; violence

Les fondements de la cartographie de Jacques Cartier : l'expérience maritime, les connaissances cosmographiques et les influences amérindiennes - Dallaire, Robert (Université de Montréal, 2000)
La représentation géographique de l'Amérique du Nord chez Jacques Cartier ne se résume pas uniquement aux quelques cartes de seconde mains datant de la première moitié du XVIe siècle. Traditionnellement, les historiens ont eu recours au témoignage de la cartographie afin de décrire la vision géographique du pilote malouin. Il appert, à la lecture de la relation des voyages de Cartier, que celui-ci avait acquis des connaissances théoriques dans l'étude de la cosmographie. Élément important de la vision géographique du capitaine breton, cette science consacrée à la description du monde n'a pas été retenue par les spécialistes afin de présenter les fondements de la cartographie de l'Amérique du Nord chez Cartier. Ainsi, ce mémoire cherche à approfondir nos connaissances sur la représentation cosmographique de l'Amérique du Nord chez Cartier et entre 1534 à 1542. Loin d'être ce vieux loup de mer illettré et navigant à l'estime, Cartier était un pilote sachant « prendre les hauteurs» et un lecteur attentif de la Coutume de Bretagne. Ses voyages au long cours l'avaient menés jusqu'à Terre-Neuve et probablement au Brésil avant même qu'il entreprenne sa première expédition officielle en 1534. Sa connaissance de la cosmographie avait fait de lui l'une des autorités en matière de navigation lointaine. Il semble que ce semeur de toponymes en terre d'Amérique ait été influencé par la théorie des climats, désirant prolonger ainsi, sur la même latitude, sa Bretagne natale au-delà de l'Atlantique. Cette vision typiquement européenne sera modifiée par la participation amérindienne aux explorations de Cartier. Ainsi, selon l'affirmation des lroquoiens de Stadaconé, le territoire compris entre la rivière des Outaouais, le Saguenay et le fleuve Saint-Laurent était une île, témoignage reflétant l'une des facettes de la géographie amérindienne.
Keywords: =CL

Familles de charpentiers et de menuisiers à Montréal au XVIIIe siècle : alliances matrimoniales et reproduction sociale - Langlois, France-Isabelle (Université de Montréal, 1996)

Un combat d'école? : le champ historiographique vu de Québec (1947-1965) - Dorais, François-Olivier (Université de Montréal, 2019)
Après les chocs de la crise des années 1930 et de la Deuxième Guerre mondiale, les conditions de production et la représentation de l'histoire du Québec entrent dans une phase de profondes mutations. Alors que s'enfièvre le débat autour des causes du « retard » de la société québécoise et l'enjeu de sa « modernisation », le savoir historique que convoque une nouvelle génération de jeunes universitaires entend offrir une nouvelle intelligibilité de l'être-ensemble francophone. L'« école historique de Québec », qui a réuni des figures historiennes majeures comme Marcel Trudel, Fernand Ouellet et Jean Hamelin, naît dans cette foulée de changements où elle configurera, dans ses querelles nourries avec l'école de Montréal, une matrice fondamentale de l'historiographie québécoise contemporaine. Objet familier de notre mémoire savante et constitutif du récit des origines de la discipline historique au Québec, l'« école de Québec » n'en demeure pas moins une sorte d'évidence héritée et non problématisée, dont la construction rétrospective dénote une finalité utilitaire et idéologique plutôt que proprement heuristique. Or, l'évidence apparente du sens que l'on a longtemps perçue dans cette « école » dissimule une complexité que cette thèse s'emploie à analyser plus finement. Qui sont Trudel, Ouellet et Hamelin? Quelle place occupent leurs travaux dans l'historiographie québécoise et canadienne? Quelles influences ont-ils agrégé? Quel « récit des origines » du groupe ont-ils accrédité? Dans quelle mesure se sont-ils mis au service d'une option politique? Face à la difficulté de parler d'une école au sens fort du terme en raison, notamment, de la variété de sa production historiographique, de l'absence d'une doctrine intellectuelle puissamment articulée chez ses membres et de la discontinuité des générations et des trajectoires individuelles qui l'ont caractérisée, notre recherche s'emploie à retracer l’histoire de ce groupe d'historiens aux contours flous, à mieux cerner son identité et situer son apport à la recomposition du champ intellectuel et historiographique québécois d'après-guerre. Notre thèse soutient que la position originale du trio lavallois fut d'avoir constitué, plutôt qu'une école de pensée, une « école d'activité » (Samuel Gilmore), organisée autour d'une conception semblable des pratiques et de la méthode historienne plutôt que d'une orthodoxie ou un modèle d'interprétation unifié et cohérent. Bien entendu, cette disposition n'a pas pour autant empêché ces historiens de se reconnaître un même « air de famille » et d'esquisser un horizon interprétatif commun. Dans une perspective alliant l'historiographie et l'histoire intellectuelle, cette étude lève le voile sur les cheminements, à la fois convergents et divergents, de trois historiens majeurs du Québec contemporain situés à l'intersection des champs universitaire, intellectuel et politique. Ce faisant, elle offre un point d'observation privilégié pour jauger les rapports évolutifs entre le savoir historique et la culture au Québec et cerner la particularité du « terreau » intellectuel lavallois dans la spécificité de ses réseaux nationaux et internationaux ainsi que de ses accointances avec la pensée antinationaliste, libérale et fédéraliste d'après-guerre.
Keywords: "Laval School"; Canada; Historians; Historiography; History - Canadian / Histoire - Canadienne (UMI : 0334); Intellectual history; Laval University; Quebec; Québec; Université Laval; histoire intellectuelle; historiens; historiographie; « école de Laval »; « école de Québec »; “Quebec School”

Les anciens captifs de Deerfield au Canada : parcours de vie et intégration - Machabée St-Georges, Annabelle (Université de Montréal, 2010)
On February 29th, 1704, a force of 250 French and Amerindian allies attacked the small border village of Deerfield, Massachusetts and kidnapped 112 inhabitants, 89 of whom made it alive to New France. At the end of the War of the Spanish Succession, 25 of these captives stayed among the French or the Amerindians. For a long time, they had the status of captives, English or simply, foreigners. This work aims to reconstitute the course of life and integration of the former Deerfield captives in the French colony. We shall first identify the participants in the attack on Deerfield. Turning our attention to the captives, we shall study the process of their integration into the colony and their assimilation by religion. We shall examine the modalities of adoption of the captives by the colonists and the Amerindians. We shall also see what was the influence of marriage on the insertion of captives into Canadian social networks. Finally, we shall analyze the social and occupational status and the social reproduction of the immediate descendants of some of these captives.
Keywords: History - Canadian / Histoire - Canadienne (UMI : 0334); assimilation; captifs; captives; conversion; integration; intégration; religion

L'État et l'espace colonial : savoirs géographiques entre la France et la Nouvelle-France aux XVIIe et XVIIIe siècles - Palomino, Jean-François (Université de Montréal, 2018)
The French monarchy accumulated a large number of geographic documents describing its colonies. The thesis submits to close examination the role of the state in an intellectual activity consisting of observing, recording and representing graphically the colonial territory. Exploiting various types of documents – topographic, cadastral, hydrographic and general maps –, the study aims not to present an inclusive portrait of cartographic activity, but rather to explore various thematic issues, notably: the bounding of colonial territory, courtiers’ cartography, validation mechanisms, specialization and useful knowledge, the uses of geographical information. With regard to a historiography increasingly preoccupied with the modes of territorial dispossession and of the inscription of knowledge, the thesis analyzes the contexts and mechanisms of the production, collection, archiving and re-use of geographical documents produced by or for the state in New France. In exploring the colonial context of imperial cartographic activity, the study confirms the importance of the state in this field. But it affords a more precise view of that activity in emphasizing the complexity of the genesis of maps that sooner or later gravitated toward the metropolitan centre.
Keywords: Canada; Cartes; Cartographie; Cartography; Dépôt des cartes et plans de la Marine; Geography; Gédéon de Catalogne; Géographique; Histoire; History; History - Canadian / Histoire - Canadienne (UMI : 0334); Jean Baptiste Louis Franquelin; Jean Deshayes; Knowledge; Mapping; Maps; New France; Nouvelle-France; Robert de Villeneuve; Savoir; State; Territoire; Territory; État

Terres de nos aïeux : la représentation du territoire historique dans l’historiographie canadienne-française - St-Pierre, Stéphanie C. (Université de Montréal, 2021)
Migratory movements from Quebec between the mid-19th century and 1930 led to the establishment of Francophone communities in various regions of North America, thus creating contexts favourable to the formulation of historical discourse. In the course of this dissertation, we analyze whether this discourse contributed to the great historical narrative of the French-Canadian nation, or if it proposed a region-specific narrative. The dissertation compares the historiography produced in Quebec to that emerging in the periphery, in Ontario, Western Canada and New England, examining more specifically the representations of historical territory and the development of a discours d’enracinement (or a sense of rootedness). This comparative study provides a better understanding of the dynamics between regions and nation that influence historical narrative in French Canadian history. Spanning more than a century, the study focuses on certain key moments in historical production in Quebec and in the selected regions we study. By drawing parallels between historical production in Quebec and in various minority settings, we examine the points of convergence and divergences between historical work in the regions and in Quebec. This dissertation therefore examines the place of the nation and the region in historical discourse, through the analysis of the discours d’enracinement or sense of rootedness, in order to understand the role it plays in Quebec’s historiography and in historical work being produced in the French Canadian diaspora until the 1960s. The objective here is to highlight regional experiences and the similarities and contrasts that have generally escaped researchers.
Keywords: Canada français; Canadian francophone communities; Canadiens français; Franco-Americans; Franco-Manitobains; Franco-Manitobans; Franco-Ontarians; Franco-Ontariens; History - Canadian / Histoire - Canadienne (UMI : 0334); Manitoba français; Nouvelle-Angleterre; Ontario français; Ouest canadien; Québec; Québécois; Western Canada; francophonie canadienne; histoire intellectuelle; historiographie; historiography; intellectual history; milieu minoritaire; minority setting; nation; nationalisme; territoire; territory

La Nouvelle-France dans le discours pastoral des évêques de l’après-Conquête - Hubert, Ollivier; Wien, Thomas; Vidale, Cécile; Frenette, Yves (De Québec à l’Amérique française. Histoire et mémoire, 2006)

Le monde rural québécois aux XVIIIe et XIXe siècles: cultures, hiérarchies, pouvoirs - Dessureault, Christian; Robichaud, Léon; Hudon, Christine; Thuot, Jean-René; Wien, Thomas (Fides, 2018)